Novel Human Induced Pluripotent Stem Cell-Based Model for Retinal Pigment Epithelial Cells to Reveal Possible Disease Mechanisms for Macular Degeneration in Pseudoxanthoma Elasticum - Taina Viheriälä; Heidi Hongisto; Lyydia Saari; Marika Oksanen; Tanja Ilmarinen; Suvi Väärämäki; Hannu Uusitalo; Pasi Nevalainen; Heli Skottman (Journal of Ophthalmology)
Pseudoxanthoma elasticum (PXE) is a rare metabolic disease with autosomal recessive inheritance. The manifestation in PXE is represented by retinal complications, pseudoxanthomas of the skin folding areas, and arterial calcification. The retinal complications are caused by the calcification of Bruch’s membrane beneath retinal pigment epithelial cells (RPE) that can lead to retinal macular degeneration. The exact mechanism for the retinal pathophysiology is not known, and patients have variable symptoms and findings. Two induced pluripotent stem cell (hiPSC) lines from a patient carrying the common homozygous mutation c.3421C > T, p.Arg1141X in the ATP-binding cassette transporter gene (ABCC6; OMIM264800) were established and fully characterized. Then, RPE cells were differentiated, and molecular and functional characterization was conducted as a comparison to healthy controls. Data demonstrated that PXE-specific high-quality hiPSC lines can be established from a skin biopsy regardless of the skin-related disease phenotype and disease-specific RPE differentiation is feasible. The molecular and functional assessment of the PXE-specific RPE indicated increased pigmentation and reduced epithelial barrier functions as well as phagocytosis activity as compared to healthy controls. Although preliminary data, this indicates possible RPE-dependent factors that might explain the individual vulnerability of the retinas for macular degeneration in PXE. Future validation of the novel findings with additional PXE patients will be important.